Improving vaccination uptake among adolescents - Abdullahi, L.H.; Kagina, B.M.; Wiysonge, C.S. (Cochrane Database of Systematic Reviews, 2020)
Adolescent vaccination has received increased attention since the Global Vaccine Action Plan's call to extend the benefits of immunisation more equitably beyond childhood. In recent years, many programmes have been launched to increase the uptake of different vaccines in adolescent populations; however, vaccination coverage among adolescents remains suboptimal. Therefore, understanding and evaluating the various interventions that can be used to improve adolescent vaccination is crucial.
Keywords: vaccination; adolescents